Building Innovation Pipelines through Computer-Aided Innovation 4th IFIP WG 5.4 Working Conference, CAI 2011, Strasbourg, France, June 30 - July 1, 2011. Proceedings - Cavallucci, Denis; Guio, Roland de.; Cascini, Gaetano; SpringeringerLink (Online service). (Berlin, Heidelberg Springer Berlin Heidelberg, 2011)
This volume constitutes the refereed proceedings of the 4th IFIP WG 5.4. Working Conference on Computer- Aided Innovation, CAI 2011, held in Strasbourg, France, in June/July 2011. The 14 revised papers presented were carefully reviewed and selected from numerous submissions. They cover a broad range of topics from basic research to industrial applications of computer-aided innovation systems.
Electronic reproduction.
Keywords: Computer science; Software engineering; Artificial intelligence; Technological innovations -- Congresses; Electronic books